STUDY OF THE INFLUENCE OF LOW TEMPERATURES IN DYNAMIC CONDITIONS ON SPECIAL MATERIALS FOR INSULATING SUITS OF CHEMICAL ENTERPRISES - MIHAILOVA, Nina; PRIVALA, Valerii (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Domestic chemical industries urgently need the creation of special high-class protective clothing to allow working in extreme conditions without endangering the lives and health of workers. In previous publications, it was determined that the necessary comprehensive protection against the effects of harmful production factors is provided by the creation and use of an insulating suit, which should become a barrier that prevents the penetration, and therefore the influence of mineral acids, alkalis, ammonia, salt solutions, etc. different concentrations. That is, it is about the creation of special clothing with the necessary level of provision and preservation of such basic protective indicators as chemical resistance and impermeability of the material while preserving the tightness of the product as a whole. Preparation equipment and fitters for cleaning closed containers for transportation and storage of aggressive environments can simultaneously be exposed not only to mineral acids, alkalis, solutions of salts based on them, but also to the remains of liquid ammonia, the evaporation of which occurs when the temperature drops, which leads to the primary destruction of the polymer coating materials of special suits. For example, local destruction in contact with liquid ammonia leads to a sharp cooling (up to - 340C) of the contact surface of the material and destruction of the polymer coating, especially during operation (in dynamics), which can lead to a violation of the tightness of the protective product. Since workers have to perform a significant number of work movements while in an insulating suit, there was a need to study such an indicator as the resistance of materials to dynamic loads in conditions of low temperatures. Research was conducted on samples of materials with a polymer coating, which belong to the class of artificial leathers for special purposes from both foreign and domestic manufacturers.